1999
DOI: 10.1076/opge.20.4.233.2267
|View full text |Cite
|
Sign up to set email alerts
|

A family with autosomal dominant distal arthrogryposis multiplex congenita and Brown syndrome

Abstract: Arthrogryposis multiplex congenita is a heterogeneous condition found in a number of different disorders and characterized by congenital joint contractures. We describe typical signs of congenital Brown syndrome (inability to elevate the affected eye actively or passively in full adduction) in three relatives with distal arthrogryposis multiplex congenita. We found a thickening of the superior oblique muscles in these patients with pain and increased intraocular pressure in upgaze. The pathogenesis of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While lack of any neurological abnormalities in our patients and their arthrogryposis strongly argued for fibrosis of the superior rectus and/or inferior oblique muscles as alternative explanation, the normal MRI leaves the exact etiology unclear. This specific combination has been described only once [Lobefalo et al, 1999]. On the other hand, there are multiple reports of the association of arthrogryposis and paresis of other extraocular muscles, for example, distal arthrogryposis type 5 [Paez et al, 1982;Zeiter and Boniuk, 1989;al-Ghamdi et al, 1997;Sahni et al, 2004].…”
Section: Discussionmentioning
confidence: 95%
“…While lack of any neurological abnormalities in our patients and their arthrogryposis strongly argued for fibrosis of the superior rectus and/or inferior oblique muscles as alternative explanation, the normal MRI leaves the exact etiology unclear. This specific combination has been described only once [Lobefalo et al, 1999]. On the other hand, there are multiple reports of the association of arthrogryposis and paresis of other extraocular muscles, for example, distal arthrogryposis type 5 [Paez et al, 1982;Zeiter and Boniuk, 1989;al-Ghamdi et al, 1997;Sahni et al, 2004].…”
Section: Discussionmentioning
confidence: 95%
“…While lack of any neurological abnormalities in our patients and their arthrogryposis strongly argued for fibrosis of the superior rectus and/or inferior oblique muscles as alternative explanation, the normal MRI leaves the exact etiology unclear. This specific combination has been described only once [Lobefalo et al, 1999]. On the other hand, there are multiple reports of the association of arthrogryposis and paresis of other extraocular muscles, for example, distal arthrogryposis type 5 [Paez et al, 1982; Zeiter and Boniuk, 1989; al‐Ghamdi et al, 1997; Sahni et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Although the superior oblique tendon is usually found to be abnormally taut (1)(2)8) , the cause of this anatomic dysfunction is still unknown, but some previously published case reports (4)(5)7,9) have suggested a genetically determined predisposition in this syndrome, consistent with recessive inheritance at the DURS1 locus and dominant inheritance with reduced penetrance at the DURS1, DURS2, and FEOM1 loci (7) . The almost perfectly symmetrical bilateral Brown's syndrome found in the here reported mother and child supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Katz et al (4) reported Brown's syndrome in monozygotic twin girls. Association with autosomal dominant pathology (5) and genetic inheritance have also been reported (6)(7) . We describe here the eye examination of two cases of bilateral Brown's syndrome occurring in mother and son.…”
Section: Introductionmentioning
confidence: 99%